Representasi Mental Disorders Lagu “Amygdala” Suga BTS Melalui Analisis Semiotika Charles Sanders Peirce - Wahyuni, Sri; Pudrianisa, Sheila Lestari Giza (AGUNA: Jurnal Ilmu Komunikasi, 2024)
Mental health disorders ones of the diseases that cannot be seen physically because someone will be attacked inwardly and even change drastically. In many young people of generation Z affected by mental health, thus making one of the BTS personnel, Suga, express it in the form of a song entitled "Amygdala" because he has experienced mental disorders. The research method used is a descriptive type of qualitative method using the semiotic analysis theory of Charles Sanders Peirce in order to provide a deeper understanding of the message of the signs in the music video related to the representation of mental disorders to the audience. In addition, this massive Korean wave made researchers use Suga BTS as an object to use the constructivism paradigm. This research refers to the analysis of signs, objects and also meanings in each scene or scene by making observations and documentation. Thus, the results of this study can represent some important meanings related to mental disorders to always think positively, be open to their surroundings, and be able to make peace with themselves not by committing suicide. So that indirectly the meaning of this song provides motivation to listeners about understanding for ourselves emotionally and as a medium to communicate to the public so that they can learn more about the representation of mental disorders.